PENDAMPINGAN PENYUSUNAN ARTIKEL ILMIAH BAGI MAHASISWA TADRIS MATEMATIKA FAKULTAS TARBIYAH UNIVERSITAS IBRAHIMY SUKOREJO SITUBONDO - Mohammad Tohir (As-Sidanah, 2024)
Mathematics education student as prospective teachers are said to be professional educators if they have pedagogical competence, personality competence, social competence, and professional competence. In this service activity, the focus of the activity is on students' professional competence as prospective mathematics teachers, namely the ability to prepare quality scientific articles. The preparation of scientific articles is carried out based on the components of complete scientific work, namely IMRAD (Introduction, Methods, Results, And Discussion). This mentoring is carried out offline with the target participants being Mathematics Tadris students, Tarbiyah Faculty, Ibrahimy University. The method used in this service activity is Participatory Action Research (PAR). The use of this method is expected to improve students' understanding and skills in compiling good and quality scientific articles. The results of the service show that students can compose quality scientific articles so that the majority of their scientific articles are published in Scopus-indexed journals/Proceedings and Sinta 3, 4 accredited journals, and non-Sinta journals.